PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASIONAL DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN (Studi Pada Karyawan Tingkat Pelaksana Perum Jasa Tirta I Wilayah Sungai Brantas dan Bengawan Solo) - M Zainal Arifin; Taher Alhabsji; Hamidah Nayati Utami (Jurnal Bisnis dan Manajemen, 2016)
The purposes is to determine the effect of workload, compensation and organizational commitment to employee performance. The method is used to explanatory research by collecting information directly from the respondent, technical sampling took by stratified proporsional Random Sampling, which using the formula from Slovin to obtained sample of 116 people from a total population of 163 people. Data was collected by questionnaires designed with Likert scale. Data analysis method used to descriptive statistical analysis and inferential statistical analysis which in this study using path analysis (path analysis). Descriptive analysis show the result (1) the average value of the variable workload of 2:28 ( disagree) with the variable workload statement, its mean that their work is easy, (2) the average value of the variable compensation of 4:13 (agree) the statement of variable compensation , its means that compensation more better, (3) the average value of variable organizational commitment at 4:36 (absolutly agree) to the statement variable organizational commitment , which means that organizational commitment is very high , (4) the average value of the variable performance at 4:19 (agree) with the statement of performance variable , which means that the employee's performance is good. The findings showed that there is a significant and positive effect between work load on organizational commitment (? = 0.434, p = 0.000), there is no significant effect and negative between workload on employees performance (? = -0020, p = 0828), there is a significant and positive effect between compensation for organizational commitment (? = 0234, p = 0.005), there is a significant and positive effect of the compensation on employees performance (? = 0282, p = 0.001), and there is a significant and positive effect between organizational commitment to employees performance (? = 0.351, p = 0.000).